Assessing intrarenal nonperfusion and vascular leakage in acute kidney injury with multinuclear 1H/19F MRI and perfluorocarbon nanoparticles. Issue 6 (8th August 2013) - Hu, Lingzhi; Chen, Junjie; Yang, Xiaoxia; Senpan, Angana; Allen, John S.; Yanaba, Noriko; Caruthers, Shelton D.; Lanza, Gregory M.; Hammerman, Marc R.; Wickline, Samuel A.
<x xml:space="preserve">Abstract</x> Purpose We sought to develop a unique sensor‐reporter approach for functional kidney imaging that employs circulating perfluorocarbon nanoparticles and multinuclear 1H/19F MRI. Methods 19F spin density weighted and T1 weighted images were used to generate quantitative functional mappings of both healthy and ischemia‐reperfusion (acute kidney injury) injured mouse kidneys. 1H blood‐oxygenation‐level‐dependent (BOLD) MRI was also employed as a supplementary approach to facilitate the comprehensive analysis of renal circulation and its pathological changes in acute kidney injury. Results Heterogeneous blood volume distributions and intrarenal oxygenation gradients were confirmed in healthy kidneys by 19F MRI. In a mouse model of acute kidney injury, 19F MRI, in conjunction with blood‐oxygenation‐level‐dependent MRI, sensitively delineated renal vascular damage and recovery. In the cortico‐medullary junction region, we observed 25% lower 19F signal (P < 0.05) and 70% longer 1H T2* (P < 0.01) in injured kidneys compared with contralateral kidneys at 24 h after initial ischemia‐reperfusion injury. We also detected 71% higher 19F signal (P < 0.01) and 40% lower 1H T2* (P < 0.05) in the renal medulla region of injured kidneys compared with contralateral uninjured kidneys. Conclusion Integrated 1H/19F MRI using perfluorocarbon nanoparticles provides a multiparametric readout of regional perfusion defects in acutely injured kidneys. Magn Reson Med 71:2186–2196, 2014. © 2013 Wiley Periodicals, Inc.